Natural organic matter - The relationship between character and treatability - Parsons, Simon A.; Jefferson, Bruce; Goslan, Emma H.; Jarvis, Peter; Fearing, David Andrew (IWA Publishing, 2004)
The characterisation and treatment of natural organic matter are becoming more important to the water utilities in the UK and around the world. This paper looks at the relationship between bulk and fractionated organic material and the performance of conventional water treatment processes.